MRI-Based Radiation-Free Method for Navigated Percutaneous Radiofrequency Trigeminal Rhizotomy - Lepski, Guilherme; Filho, Paulo Moacir Mesquita; Ramina, Kristofer; Bisdas, Sotirios; Ernemann, Ulrike; Tatagiba, Marcos; Morgalla, Matthias; Feigl, Guenther (Journal of Neurological Surgery Part A: Central European Neurosurgery, 2015)
Background/Study Aims Percutaneous radiofrequency trigeminal rhizotomy (RTR) is a standardized treatment for trigeminal neuralgia, yet it has been associated with serious complications related to the cannulation of the foramen ovale. Some of these complications, such as carotid injury, are potentially lethal. Neuronavigation was recently proposed as a method to increase the procedure's safety. All of the techniques described so far rely on pre- or intraoperative computed tomography scanning. Here we present a simple method based on magnetic resonance imaging (MRI) (radiation free) used to target the foramen ovale under navigation guidance.Patients/Material and Methods We retrospectively analyzed nine patients who had undergone navigated percutaneous RTR based solely on preoperative MRI and compared them with 35 patients who underwent conventional RTR guided by fluoroscopy. We analyzed immediate and late outcome and categorized the results into pain free, > 70% pain reduction, and persistent pain. We also compared groups in terms of the duration of the procedure and the complication rates. Here we describe the navigation method in detail and review the anatomical landmarks for target definition.Results The duration of the surgical procedure was similar in both groups (32.1 in the standard technique versus 34.5 minutes with navigation; p = 0.5157). There was no significant difference between groups regarding pain reduction at the immediate (p = 1.0) or late follow-up (p = 0.6284) time points. Furthermore, no serious complications were observed in the navigated group.Conclusions We present a simple radiation-free method for neuronavigation-assisted percutaneous RTR. This method proved to be safe and effective, and it is especially recommended for young, inexperienced neurosurgeons.
Keywords: trigeminal neuralgia; neuronavigation; high-resolution MRI; percutaneous rhizotomy